PENGARUH FINANCIAL DISTRESS, UKURAN PERUSAHAAN, DAN PERGANTIAN KOMITE AUDIT TERHADAP AUDITOR SWITCHING - Simatupang, Timothy Halomoan Asido; Tanusdjaja, Hendang (Jurnal Paradigma Akuntansi, 2024)
This research aims to determine the extent to which companies will replace their auditors if they experience a decrease in financial capacity, changes in company size, and changes in the audit committee at companies listed on the Indonesia Stock Exchange with the stock index code KOMPAS100 using the 2019-2021 financial statements. The sample was selected by purposive sampling method and the valid data were 64 companies. The data processing technique uses logistic regression analysis assisted by the SPSS (Statistical Product and Service Solution) program for Windows with version 25 and Microsoft Excel 2019. The results of this study indicate that financial distress and company size do not have a significant effect on auditor turnover. Meanwhile, audit committee turnover has a significant effect on auditor turnover. The implication of the research conducted is the need for supervision of the board of commissioners on audit committee changes that affect auditor turnover for the company. And make the company not careless and still maintain a positive image.